STRATEGI PEMASARAN BUAH MANGGIS PADA KELOMPOKTANI SINAR MUSTIKA PUSPAHIANG DI KABUPETAN TASIKMALAYA - Ulpah Jakiyah; Budhi Wahyu Fitriadi (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Total production of the mangosteen fruit in Tasikmalaya Regency achieve 345 tons in 2017 (Department of Agriculture Kabupaten Tasikmalaya 2017). Mangosteen fruit from the city of Tasikmalaya has export market opportunities are quite large. Export demand is high resulting in farmers group Sinar Mustika made a new breakthrough by doing organic certification for mangosteen. This is done to increase the selling price and has the power market. The selling price of the mangosteen fruit from each marketing agencies have a range which is quite high. So the purpose of this research is to formulate a marketing strategy mangosteen tools through the concept of the marketing mix. The design of the marketing mix involves the internal and external conditions, farmers group Sinar Mustika. The method of analysis with AHP (Analitical Hierarchy Process) is used for research in determining which strategy to become a priority in the marketing activities of mangosteen. Stages of the research carried out among others 1) to collect marketing information mangosteen with through observation, survey, and interview. 2) gather information about the advantages and weaknesses of the marketing activities of mangosteen in Tasikmalaya Regency, 3) formulate a strategy for the development of mangosteen organic with AHP (Analitical Hierarchy Process). Marketing mangosteen organic has two marketing channels involve two distributors which is PT Java Fresh and PT Anugrah Lalang Buana. Every marketing actors involved do not make changes on mangosteen but marketing in the form of fresh mangosteen. According to the internal and external conditions, farmers group Sinar Mustika have the value of the X axis 0.58 and the Y-axis 0.22 is in quadrant 1. Shows the position of the group must continue to concentrate on the current market (market penetration and market development) and product. While alternative strategies beradasrkan AHP that farmer groups should do the strategy in improving the quality of post-harvest with the highest weight value 0.39. Therefore the group should cooperate with local authorities in the provision of resources in increasing the quality of the product and market development to be able to reduce the risk of mangosteen.